Relative age effect, morphological status and physical performance of U-15 Croatian football players - Ante Rađa; Jakov Marasović; Marko Erceg; Peter Krustrup; Morten B. Randers; Luca Paolo Ardigò (PLoS ONE, 2025)
The relative age effect (RAE) refers to the unequal quartal-to-quartal birth distribution in competitive sports, leading to more athletes being born earlier in the selection period. This effect results in relatively older players, who are often physically more developed, being overrepresented in youth academies and professional levels, as they receive more attention and opportunities due to their advanced biological maturation and superior physical performance compared to their younger peers. This study involved 177 U-15 football players from Dalmatia, Croatia, averaging 14.1 ± 0.9 yrs of age and 6.6 ± 1.9 yrs of training experience. Anthropometric characteristics, motor-functional abilities, and specific abilities with the ball were measured over two days, using standardised equipment and procedures, and the data were analysed with descriptive statistics, one-way analysis of variance, and post hoc least significant difference tests to identify differences across quartiles. The study found statistically significant differences in the distribution and characteristics of players born in different quartiles of the year, with 63.3% born in the first two quartiles. RAE influenced young football players’ birth distribution and physical characteristics, with a higher proportion born in the first quartile of the year (Q1) and showing superior morphological development and physical performance. Q1 players were significantly taller and heavier and performed better in explosiveness tests (medium effect sizes) compared to other quartiles. Furthermore, small to medium effect differences occurred in circumferences, 20-m, 30-m sprints and ball-kicking velocities in favour of Q1. As these abilities and characteristics are key to success in football, players born in the first quartile have an advantage in the selection process. This highlights the need for coaches to focus on potential talent rather than current performance despite the competitive pressure to win.